A critical review of cascading failure analysis and modeling of power system. (December 2017) - Guo, Hengdao; Zheng, Ciyan; Iu, Herbert Ho-Ching; Fernando, Tyrone
Abstract: Cascading failure analysis in power systems draws a wide attention from researchers due to frequent occurrence of blackouts all over the world during past decades. A variety of mathematical models and analysis tools have been proposed in order to better understand the complicated mechanisms during the cascading failure. This paper provides a brief overview on cascading failure analysis and categorizes the most relevant literatures and analysis models. Different features related to cascading failures have been demonstrated and discussed. Comparisons between different models have been presented. Advantages and disadvantages of these models are summarized. The paper also highlights the possible future trends.